2004
DOI: 10.1159/000071281
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Taste Acuity in Patients with Diabetes mellitus on Maintenance Hemodialysis

Abstract: Aims: It has been reported that taste acuity for the four primary tastes, sour, sweet, salty and bitter, is impaired in hemodialysis (HD) patients. However, there have been no studies reported on taste acuity of diabetic HD patients. The present study aimed to quantify and compare the taste acuity of diabetic and non-diabetic HD patients, and further to determine if there were correlations between diminished taste acuity and certain blood serum parameters typically askew in hemodialysis patients. Methods: In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Taste disturbances have been reported in patients with diabetes mellitus, 3 but all investigators have not observed this finding. Although patients with diabetes who receive hemodialysis have been reported to have altered taste, 7 it is a complex symptom, and it may be related to salivary flow and changes in food intake associated with disease management. Other neurosensory disorders of the oral and perioral tissues, including burning mouth syndrome and dysphagia, have been reported in patients with diabetes.…”
Section: Oral Manifestations Of Diabetes Mellitusmentioning
confidence: 99%
“…Taste disturbances have been reported in patients with diabetes mellitus, 3 but all investigators have not observed this finding. Although patients with diabetes who receive hemodialysis have been reported to have altered taste, 7 it is a complex symptom, and it may be related to salivary flow and changes in food intake associated with disease management. Other neurosensory disorders of the oral and perioral tissues, including burning mouth syndrome and dysphagia, have been reported in patients with diabetes.…”
Section: Oral Manifestations Of Diabetes Mellitusmentioning
confidence: 99%
“…Assessment of taste disorders: In order to quantitatively determine taste disorders, a commercial assay kit, Taste Disk ® (Sanwa Chemicals, Nagoya, Japan), which has been produced based on the report by Tomita et al (10), was used. The test was done according to the procedure recommended by the manufacturer, which has already been reported in many studies examining taste disorders (11)(12)(13)(14)(15). The subjects were required not to eat or smoke for two hours prior to the taste test.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, satisfying meals are very important for enhancing quality of life. The decline in taste sensation that occurs in old age is thought to be caused by various factors such as atrophy of taste buds, dental and systemic deterioration, and multiple medications (1–3). Doty and Bromley (1) suggested that medications not only have a perceivable taste themselves at times, but they can alter the mechanisms responsible for the ultimate perception of tastes and smells.…”
Section: Introductionmentioning
confidence: 99%
“…Bergasa (2) described a hypothesis for a brain‐mediated mechanism underlying taste alterations in hepatic disorders. Matsuo et al (3) concluded that taste acuity is partially impaired in diabetic haemodialysis patients. Nonetheless, the mechanism involved has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%